Blood Donation Management Application on Android Platform - Piraviendran Rajendran,; Othman, Muhaini; Siti Aisyah Mohamed, (Applied Information Technology And Computer Science, 2021)
Mobile-Based Red Donor Application System is an application which would help blood bank department to manage the donation events occur smoothly. The retrieval of blood donors’ records and blood stocks-related data are easier through this application. This application allows user and the hospital staff to register all the donors, manage blood collection details and blood type issued details. This android project provides the easiest and fastest way to search for blood donors’ details via their identification number. The adaptation of mobile-based technology, which are Android Studio, Firebase database and Java language is implemented during the system construction. The application is also designed to support the government hospital to meet the demand of blood by collecting the information about the possible volunteer donors and keep their records safely. The application is expected to assist hospital staffs involved during blood donation events by easily manage donors’ data.